A Critical Perspective Analysis Of Indonesian Accounting Thought: Some Preliminary Thoughts On The Search For Better Understanding Of Accounting In Practice - Sukoharsono, Eko Ganis (The International Journal of Accounting and Business Society, 2005)
This paper provides some preliminary thoughts on a long-term qualitative research project investigating the development of Indonesian accounting thought. The first thought is to explicate accounting and its relation to the existing sociological perspective. Western and Indonesian sociological perspective are includes in analyses. The second thought is that the understanding of historical development of accounting in Indonesian is significantly needed for deeper analyses on the current development and problems of Indonesian accounting. It is also argued that accounting colonialism‟s legacy has much shaped the models of Indonesian accounting today. The third thought is that given the adoption of critical perspective, accounting in practice provides a richer picture. For example, accounting can be viewed as a central to the process of reality construction within an organization, shaping decision making in accordance with the value and perspective of the organizational and social reality.